2016
DOI: 10.1097/brs.0000000000001347
|View full text |Cite
|
Sign up to set email alerts
|

Osteoporosis in Cervical Spine Surgery

Abstract: 3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(48 citation statements)
references
References 26 publications
0
48
0
Order By: Relevance
“…Osteoporosis affects a significant number of Americans, with the highest prevalence among the older adults and women [10]. Patients with osteoporosis have associated increases in comorbidities, and those undergoing spine surgery are at a greater risk for fusion construct failure and pseudoarthrosis [22]. Treating surgeons must identify patients at risk for osteoporosis and initiate medical optimization before surgery.…”
Section: Resultsmentioning
confidence: 99%
“…Osteoporosis affects a significant number of Americans, with the highest prevalence among the older adults and women [10]. Patients with osteoporosis have associated increases in comorbidities, and those undergoing spine surgery are at a greater risk for fusion construct failure and pseudoarthrosis [22]. Treating surgeons must identify patients at risk for osteoporosis and initiate medical optimization before surgery.…”
Section: Resultsmentioning
confidence: 99%
“…Osteoporosis can negatively affect cervical spine surgery and postoperative rehabilitation. In patients undergoing surgery due to degenerative cervical spine disorders, osteoporosis patients are more likely to receive posterior cervical fusion surgery than non osteoporosis patients; also, they tend to have more postoperative bleeding, higher probability of revision surgery, longer hospital stay, and higher hospitalization expenditure [9] .…”
Section: Discussionmentioning
confidence: 99%
“…9 In a review of immediate postoperative complications in osteoporotic patients specifically undergoing cervical spine surgery, the authors identified a higher rate of hemorrhage (odds ratio [OR] 1.7), an increased mean length of inpatient postoperative stay by one full day, and nearly 30% higher mean surgeryrelated costs compared to nonosteoporotic patients. 25 This significant and often increased incidence of complications in osteoporotic patients receiving spinal surgery is both dangerous and often manifests in the increased need for surgical revision. In the literature reviewing spinal fusion procedures, rates of nonunion in both osteoporotic and nonosteoporotic patients have been reported between as low as 5% and as high as 35%.…”
Section: Impact Of Osteoporosis On Surgical Outcomesmentioning
confidence: 99%